2012
DOI: 10.3917/ridp.823.0457
|View full text |Cite
|
Sign up to set email alerts
|

The principle of humanity in penal law

Abstract: Distribution électronique Cairn.info pour Érès. © Érès. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalable et écrit de l'éd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…We have adjusted the measured DV's of these works appropriately to be quoted in terms of our fiducial Patchy sound horizon. Both of our distance scales are within at most 0.5σ of the Anderson et al (2014), Cuesta et al (2016), andGil-Marín et al (2016) measurements. Our slightly larger error bars reflect that we achieve a precision of roughly 1.4% (statistical) on the distance scale while the 2PCF measurements achieve a precision of roughly 1.0%.…”
Section: Bao Detectionsupporting
confidence: 83%
See 2 more Smart Citations
“…We have adjusted the measured DV's of these works appropriately to be quoted in terms of our fiducial Patchy sound horizon. Both of our distance scales are within at most 0.5σ of the Anderson et al (2014), Cuesta et al (2016), andGil-Marín et al (2016) measurements. Our slightly larger error bars reflect that we achieve a precision of roughly 1.4% (statistical) on the distance scale while the 2PCF measurements achieve a precision of roughly 1.0%.…”
Section: Bao Detectionsupporting
confidence: 83%
“…while from the SDSS DR12 CMASS 2PCF including reconstruction, Cuesta et al (2016) found DV, Cuesta(zsurvey ) = 2036 ± 21 Mpc…”
Section: Bao Detectionmentioning
confidence: 96%
See 1 more Smart Citation
“…The resulting MD-Patchy mocks reproduce the number density, selection function, survey geometry, multipole power spectrum, multipole correlation function and three point statistics of the BOSS DR11 CMASS sample. The MD-Patchy mock catalogs have been tested and applied on the analysis of BOSS galaxy surveys (Chuang et al 2013(Chuang et al , 2016Cuesta et al 2016).…”
Section: Mock Catalogs To Measure the Covariance Matrixmentioning
confidence: 99%
“…Beutler et al (2016) compared different redshift slices within the Baryon Oscillation Spectroscopic Survey (BOSS) and WiggleZ to look for the relative velocity effect and found no evidence for it. Higher precision constraints are required: Blazek, McEwen & Hirata (2016) show that even a relative velocity bias of order 4% of the linear bias can cause a 1% shift in the distance scale, comparable with the statistical errors on the lastest BOSS measurement (Cuesta et al 2016;Gil-Marín et al 2016;Alam et al 2016). Further, Dark Energy Spectroscopic Instrument (DESI; Levi et al 2013), with first light in 2019, will improve on the BOSS error bars by roughly a factor of five, so even a relative velocity bias that is 1% of the linear bias could systematically shift the distance scale comparably to DESI's statistical error bars.…”
Section: Introductionmentioning
confidence: 99%